Kandungan Logam Berat Timbal (Pb) dan Kadmium (Cd) pada Beberapa Jenis Krustasea Di Pantai Batakan dan Takisung Kabupaten Tanah Laut Kalimantan Selatan - Aditya Rahman (Bioscientiae, 2006)
South Kalimantan province has huge natural resources Tanah Laut regency is one of the regencies in this province. This research is aimed to define the contents of Pb and Cd heavy metal in Crustaceae (shrimp and crab) of the Takisung and Batakan coasts in Tanah Laut regency, South Kalimantan.  Sampling was done twice with duplo method.  Pb and Cd content of the crustaceans was measured with AAS.  The result  showed a high contamination levels which were 42 – 125 ppm for Pb and 8 – 17 ppm for Cd, indicating that the contamination had exceeded the normal threshold (2 ppm for Pb and 1 ppm for Cd). It could be concluded that Takisung and Batakan Coast has been contaminated with heavy metals.